2013
DOI: 10.4236/ojpsych.2013.31a013
|View full text |Cite
|
Sign up to set email alerts
|

Reducing parental anxiety using a family based intervention for youth mental health: A randomized controlled trial

Abstract: This paper presents findings on parent anxiety and attachment relationship style from the Deakin Family Options (DFO) pilot study, a randomized controlled pilot study comparing a family-based treatment (BEST Plus), versus a youth only treatment (CBT) versus a group who received both of these treatments (COM-BINED). Eligible participants were families with a young person (aged 12 -25 years) with a high prevalence mental health problem. Youth from participating families scored in the clinical or subclinical rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(77 reference statements)
2
4
0
Order By: Relevance
“…These findings reinforce the potential benefits of familybased interventions targeting CMH in improving PMH and wellbeing (Bertino et al, 2013;Cluxton-Keller et al, 2015;Poole et al, 2018), though further analysis is necessary to determine whether this extends to clinical levels of depression and anxiety in parents. These findings reinforce the potential benefits of familybased interventions targeting CMH in improving PMH and wellbeing (Bertino et al, 2013;Cluxton-Keller et al, 2015;Poole et al, 2018), though further analysis is necessary to determine whether this extends to clinical levels of depression and anxiety in parents.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…These findings reinforce the potential benefits of familybased interventions targeting CMH in improving PMH and wellbeing (Bertino et al, 2013;Cluxton-Keller et al, 2015;Poole et al, 2018), though further analysis is necessary to determine whether this extends to clinical levels of depression and anxiety in parents. These findings reinforce the potential benefits of familybased interventions targeting CMH in improving PMH and wellbeing (Bertino et al, 2013;Cluxton-Keller et al, 2015;Poole et al, 2018), though further analysis is necessary to determine whether this extends to clinical levels of depression and anxiety in parents.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, results were also indicative of a significant reduction in parental psychological distress post-program and at follow-up; however, these effects did not maintain significance when comparing the 8-and 14-session SFC. These findings reinforce the potential benefits of familybased interventions targeting CMH in improving PMH and wellbeing (Bertino et al, 2013;Cluxton-Keller et al, 2015;Poole et al, 2018), though further analysis is necessary to determine whether this extends to clinical levels of depression and anxiety in parents.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Clinical trials our team have being running in Australia have accumulated good evidence to show that the approach can effectively treat a range of adolescent mental disorders. The studies show that improvement in adolescent mental health is typically accompanied by improvements in family functioning and notably improvements in the parent's mental health (2)(3)(4)(5)(6)(7)(8). Previously our research group has also published qualitative studies of participant experiences as well as a description of the main features of the program for the treatment of adolescent depression called BEST-Mood (5,9,10).…”
mentioning
confidence: 99%
“…Such outcomes were also observed in a pilot study that evaluated the BEST Plus program ( N = 34), which also reported improved family cohesion, and increased youth motivation and action to address their mental health issues (Bamberg et al., ). Parental depression and anxiety were also shown to reduce significantly in response to BEST Plus in a randomized controlled pilot study ( N = 48) that compared a youth only CBT group, versus a BEST Plus condition, versus a combined group who received both BEST Plus and CBT treatments (Bertino et al., ).…”
Section: The Behaviour Exchange and Systems Therapy—mood Programmentioning
confidence: 99%